Análisis de la calidad de absorción visual de las unidades del paisaje de la laguna Limpiopungo del parque nacional Cotopaxi, propuesta de conservación, 2023. - Caizaluisa Arequipa, Edison David (2023)
The current research project was carried out with the objective to determine the visual quality absorption of landscape units in Limpiopungo lagoon in Cotopaxi National Park, Cotopaxi province. A methodology focused on the identification of landscape units was used based on the guidelines indicated by Bureau Land Management (BLM) method (VRM) for visual quality determination, visual absorption quality (CAV), fragility and visual sensitivity. The qualitative approach was established and identified through photographs, allowing evaluation of each criteria and specific components within the visual evaluation of landscape through the analysis of registered photographs about study area. In order to obtain the photographs, in-site visits to the field were made. Among obtained results, it was determined that lagoon moorland has an average visual quality of class B; the visual absorption capacity is class II, with visual sensitivity of class 4 with low quality and medium-high CAV and visual fragility has an average of 20, which places the moorland in Class II with moderate fragility; therefore, it is essential to propose a conservation plan for Limpiopungo Lagoon moorland of Cotopaxi National Park.